Effect of Therapeutic Ultrasound on Human Periodontal Ligament Cells for Dental and Periodontal Tissue Engineering - El-Bialy, Tarek (Bentham Open, 2012)
The objective of this study was to investigate whether low intensity pulsed ultrasound (LIPUS) has anabolic effects on human periodontal ligament (PDL) cells. The PDL cells were plated in 48-well plates and cultured at 37°C in an atmosphere of 5% CO2 in air, in a humidified incubator until confluent. The cells were divided into three groups including control, 5 min and 10 min ultrasound application. The LIPUS was applied using a 2.5 transducer that produces an incident intensity of 30 mW/cm2 of the transducer's surface area. The results from the quantitative polymerase chain reaction (PCR) indicates that expression levels of alkaline phosphatase (ALP),cyclin D1 (CYC), nucleostemin (NCT) were increased after four weeks of 10 minutes of daily ultrasound treatment. The increased ALP/DNA by LIPUS shows a time dependent pattern with the highest activity occurring after four weeks of treatment. These results demonstrate that LIPUS has an anabolic effect on PDL cells and suggest that LIPUS may enhance the pluripotent characteristics of PDL cells as indicated by the up-regulation of NCT, a stem marker. These results also may explain the potential role of LIPUS in periodontal tissue regeneration.